2011
DOI: 10.1016/j.jcis.2011.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of montmorillonite tactoid size on Na–Ca cation exchange reactions

Abstract: The spatial organisation of swelling clay platelets in a suspension depends on the chemical composition of the equilibration solution. Individual clay platelets can be well dispersed, with surfaces entirely in contact with the external solution, or be stacked in tactoids, where part of the surfaces forms parallel alignments embedding interlayer water and cations. External and interlayer surfaces do not exhibit similar affinities for cations having different hydration and charge properties and the clay platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 91 publications
1
46
0
1
Order By: Relevance
“…The results are summarized in Table 4. According to literature, the clay aggregate dimensions reported in this work are plausible (Schramm and Kwak, 1982a, b;Sposito, 1992;Plaschke et al, 2001;Hauser et al, 2002;Missana et al, 2003;Tournassat et al, 2003;Bergaya et al, 2006;Bouby et al, 2011;Tournassat et al, 2011). The aspect ratio values determined agree with literature data (Plaschke et al, 2001;Tournassat et al, 2003;Cadene et al, 2005;Gélinas and Vidal, 2010;Tournassat et al, 2011;Ali and Bandyopadhyay, 2013;Veghte and Freedman, 2014;Weber et al, 2014).…”
Section: Samplesupporting
confidence: 88%
“…The results are summarized in Table 4. According to literature, the clay aggregate dimensions reported in this work are plausible (Schramm and Kwak, 1982a, b;Sposito, 1992;Plaschke et al, 2001;Hauser et al, 2002;Missana et al, 2003;Tournassat et al, 2003;Bergaya et al, 2006;Bouby et al, 2011;Tournassat et al, 2011). The aspect ratio values determined agree with literature data (Plaschke et al, 2001;Tournassat et al, 2003;Cadene et al, 2005;Gélinas and Vidal, 2010;Tournassat et al, 2011;Ali and Bandyopadhyay, 2013;Veghte and Freedman, 2014;Weber et al, 2014).…”
Section: Samplesupporting
confidence: 88%
“…The results qualitatively showed that the cations in aqueous solutions acted as the agent for the desorption of surface adsorbed 63 Ni(II) from Na-montmorillonite, although the desorption behaviors were different between divalent cations and monovalent cations. The spatial organization of montmorillonite platelet, i.e., quasicrystal or tactoid formation, was generally occurred in the presence of electrolyte cations [42]. The large tactoid formation of Na-montmorillonite could lead to the hysteresis of cation exchanges [43].…”
Section: Effect Of Electrolyte Cations Concentrationsmentioning
confidence: 99%
“…Soil OC at the sampling points (Table 2, Figure 2) ranged from 7.41 g hg -1 (C) to 7.75 g hg -1 (A), well above the values of 0.7 g hg -1 and 4.2 g hg -1 measured in the same cemetery by Tournassat et al (2011) and Stutter et al (2013), respectively. Such a high OC level in the soil might interfere with the contamination of the deeper layers of the profile; however, this would also depend on the levels of clay present, i.e., the greater the clay content, the lower the soil's cation exchange capacity (Goren et al, 2011).…”
Section: Physicochemical and Microbiological Analyses Carried Out On mentioning
confidence: 59%
“…Although pH values were close to neutrality, the highest alkalinity occurred at point C, consistent with an inefficiency in OM decomposition (Tournassat et al, 2011;Stutter et al, 2013).…”
Section: Physicochemical and Microbiological Analyses Carried Out On mentioning
confidence: 88%